Haploinsufficiency of TBK1 causes familial ALS and fronto-temporal dementia - Freischmidt, Axel; Wieland, Thomas; Richter, Benjamin; Ruf, Wolfgang; Schaeffer, Veronique; Müller, Kathrin; Marroquin, Nicolai; Nordin, Frida; Hübers, Annemarie; Weydt, Patrick; Pinto, Susana; Press, Rayomond; et al. (Nature neuroscience, 2015)
The authors show that haploinsufficiency of TBK1 causes familial forms of the neurodegenerative diseases ALS and FTD. Loss of binding of a TBK1 protein interaction domain to optineurin, a protein previously linked to ALS, is sufficient to cause the disease. Both proteins regulate autophagy and inflammation.